Development of SMS Mobile Technology for M-Learning for Distance Learners - Ismail, Issham Bin; M.Idrus, Rozhan (International Journal of Interactive Mobile Technologies (iJIM), 2008)
The evolution of technologies as well as Internet application has created new ways of communication which gives impact to all regions and sectors including educators and learners in Higher-Education Learning institutions in Malaysia. Virtual learning environments as well as e-learning applications are some of pedagogical mechanisms which may sound easy and quick to be applied but unfortunately they are rarely used. This research attempts to introduce m-Learning as â??Convenience Education